Mathematical Modelling in Basic Education: a study based on educational products from the southern of Brazil - Aguiar, Geovani Nunes; Figueiredo, Thiago Bezerra; Sousa, Bárbara Nivalda Palharini Alvim (Revista Brasileira de Educação em Ciências e Educação Matemática, 2023)
This paper addresses a literature review on educational products developed for Basic Education whose focus is on the Mathematical Modelling use. Educational products were selected over a period of five years and are the result of postgraduate programs at the professionals master’s and doctoral level, in the field of Teaching, located in the southern part of Brazil. Guided by the research question: How are Mathematical Modeling activities treated in educational products on Mathematical Modeling in programs in the South region of Brazil aimed at Basic Education? Data collection and analytical process followed the methodological assumptions of the Systematic Literature Review. In the results, we highlight different uses of Mathematical Modeling in Basic Education and articulations with different theoretical conceptions, in which we synthesize the way in which mathematical modeling activities are approached in educational products with guidelines for the different schooling stages: Early Childhood Education, Elementary School Early Years, Elementary School Final Years and High School.